Polysomnography in children with obstructive sleep apnoea and neurocognitive disorders. (16th September 2020) - Chandrakantan, Arvind; Patel, Deep; Glaun, Mica; Mehta, Deepak; Musso, Mary F.; Patel, Amee; Adler, Adam C.
Abstract: Objective: The neurocognitive associations in paediatric obstructive sleep apnoea (OSA) are well known; however, whether polysomnographic features can predict these associations is unknown. Therefore, the primary objective of this study was to compare common polysomnographic parameters in children with OSA in the presence and absence of neurocognitive dysfunction. Methods: Polysomnography data for children ages 3‐6 years with mild‐moderate OSA who as defined by AHI between 5 and 10 were analysed from a single sleep centre at a tertiary paediatric hospital from January 2016 to December 2018. The following parameters were identified: arousals per hour, percentage of time asleep, apnoea‐hypopnoea index (AHI), oxygen desaturation nadir during sleeps, baseline oxygen saturation during sleep, time spent with SpO2 less than 90%, maximum transcutaneous CO2, per cent of the total sleep time spent with TcCO2 greater than 50 mmHg, age, body mass index (BMI), gender and type of disability in the neurocognitive dysfunction group. Neurocognitive diagnoses were recorded. Those with syndromic comorbidities were excluded. The study cohort was then compared to a cohort of 200 subjects with OSA and no neurocognitive disorders matched for age, gender and BMI. A paired column analysis by chi‐squared analysis was then undertaken between the two groups. Results: A total of 200 children were identified (126 males and 74 females) in the neurocognitive dysfunction group (OSA with neurocognitive dysfunction) and compared with 200 children in the control group (OSA without neurocognitive dysfunction) (113 males and 87 females). There were no statistical differences between groups. Conclusion: Commonly used polysomnographic indices are not predictive of neurocognitive dysfunction in paediatric OSA.